The Beau monde : fashionable society in Georgian London - Greig, Hannah (Oxford University Press, 2013)
Caricatured for extravagance, vanity, glamorous celebrity and, all too often, embroiled in scandal and gossip, 18th-century London's fashionable society had a well-deserved reputation for frivolity. But to be fashionable in 1700s London meant more than simply being well dressed. Fashion denoted membership of a new type of society - the beau monde, a world where status was no longer determined by coronets and countryseats alone but by the more nebulous qualification of metropolitan 'fashion'. Conspicuous consumption and display were crucial; the right address, the right dinner guests, the right possessions, the right jewels, the right seat at the opera. The author leads us on a tour of this exciting new world, from court and parliament to London's parks, pleasure grounds, and private homes.--publisher's description.